To compare the clinical efficacy and side effects of implant (JADELLE) and IUCD (COPPER T) - Sadaf, Rabeea; Nazir, Laila; Samreen; Muddassir, Saman; Bashir, Engineer Abdul; Jehangir, Kiran (International journal of health sciences, 2023)
This study aims to compare the performance and side effects of the subdermal implant JADELLE and intrauterine contraceptive device Copper-T as long-acting reversible contraceptive methods. The study design involved a comparative analysis of Jadelle and Copper-T contraceptives, assessing clinical performance and side effects. Sample data from 336 participants was collected using stratified random sampling, with standardized instruments for demographic information, clinical assessment, and contraceptive side effects. Inclusion criteria were reproductive-age multipara women, while exclusion criteria included primary para, preexisting medical disorders, nullipara, and other contraceptive use. Ethical guidelines were followed, ensuring informed consent, privacy, and the right to withdraw. Statistical analysis employed descriptive statistics, chi-square test, independent samples t-test, and Kaplan-Meier survival analysis. SPSS (version 23.0) was used for analysis. The comparison between Group A (Jadelle) and Group B (Copper-T) reveals interesting findings. Group A has a higher mean age, but no significant differences in parity, blood pressure, or weight. Group B has more total and ongoing pregnancies. Group A experiences higher prevalence of side effects, including expulsion, infection, severe menstrual changes, pain or discomfort, and mood swings. Blood parameters show no significant differences. Variations exist in follow-up rates, informed consent, and privacy maintenance.